Surface micromorphology and fractal geometry of Co/CP/X (X = Cu, Ti, SM and Ni) nanoflake electrocatalysts - lu, tefan; Solaymani, Shahram; Bramowicz, Miroslaw; Naseri, Naimeh; Kulesza, Slawomir; Ghaderi, Atefeh (RSC advances, 2016)
This paper analyses the three-dimensional (3-D) surface texture of Co/CP/X (X = Cu, Ti, SM and Ni, CP: carbonaceous paste) nanoflakes prepared electrochemically using a conventional three electrode system. The surface chemical composition of the samples was investigated by X-ray photoelectron spectroscopy (XPS). Surface images were recorded using scanning electron microscopy (SEM) and analyzed by means of the fractal geometry. Statistical, fractal and functional surface properties of the prepared samples were computed. The statistical functions applied to the SEM data were employed in order to characterise the surfaces topographically (in amplitude, spatial distribution and pattern of surface characteristics). The analysis of the 3-D surface texture of Co/CP/X nanoflakes is essential to control the surface topography and for the correct interpretation of surface topographic features as well as its functional role. It also provides a compact representation of complex micromorphology information. This paper analyses the three-dimensional (3-D) surface texture of Co/CP/X (X = Cu, Ti, SM and Ni, CP: carbonaceous paste) nanoflakes prepared electrochemically using a conventional three electrode system.